2022
DOI: 10.3233/bmr-200208
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the force perception in knee flexor/ extensor muscles in patients with anterior cruciate ligament injury and healthy subjects

Abstract: BACKGROUND: Force perception as a contributor to the neuromuscular control of the knee joint may be altered after anterior cruciate ligament (ACL) injury. OBJECTIVE: This study aimed to compare the force perception accuracy in the knee joints of patients with ACL injury and healthy subjects. METHODS: Twenty-six patients with ACL injury and 26 healthy subjects participated in this case-control study. Participants were asked to produce 50% of the maximum voluntary isometric contraction of the knee muscles as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…ACL injury is one of the common knee joint injuries in clinic, accounting for about 80% of knee joint ligament injuries, mostly in sports injuries, and nonsports injuries account for 27.2% [14]. According to statistics, the annual incidence of ACL injury in the general population of the United States is 1 to 3 000, while the incidence of ACL injury in sports is even higher: 60/100000 for football players and 70/100000 for skiers [15]. The probability of ACL injury in female athletes is four times higher compared to men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACL injury is one of the common knee joint injuries in clinic, accounting for about 80% of knee joint ligament injuries, mostly in sports injuries, and nonsports injuries account for 27.2% [14]. According to statistics, the annual incidence of ACL injury in the general population of the United States is 1 to 3 000, while the incidence of ACL injury in sports is even higher: 60/100000 for football players and 70/100000 for skiers [15]. The probability of ACL injury in female athletes is four times higher compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of ACL injury in active service athletes in China is 0.43%, with the improvement of living standards and health concepts. As more people participate in physical exercise, the probability of ACL injury increases [15]. ACL is an important anatomical structure in the knee joint, which starts from the anterior medial side of the tibial intercondylar eminence and ends at the back of the lateral wall of the intercondylar fossa.…”
Section: Discussionmentioning
confidence: 99%
“…Besides peripheral muscular strength, the performance of CMJ requires high degrees of motor unit recruitment and frequency of nerve pulse delivery. [27][28][29] One session of intaking hydrogen, which though can facilitate local ROS clearance promoting muscle fatigue recovery, may not induce signi cant improvements in CMJ performance, which depends upon multiple neurophysiological elements. Still, we observed that H 2 inhalation before sleep signi cantly improved the MVIC and muscle force perception.…”
Section: Discussionmentioning
confidence: 99%